Countering al Qaeda : an appreciation of the situation and suggestions for strategy - Jenkins, Brian Michael (RAND, 2002)
Having achieved its initial goals in the war on terrorism, the United States is now in a second, more complex phase of the campaign. This monograph reviews events since the attacks of September 11, 2001, and discusses the current state of the al Qaeda organization and the kinds of actions that can be expected of it in the foreseeable future. Because al Qaeda constitutes the most serious immediate threat to the security of the United States, it is imperative that the campaign against terrorism remain focused and pragmatic. This monograph outlines and describes the essential, central elements that must be emphasized in this campaign, the ultimate aim of which is the destruction of a terrorist enterprise that threatens American security and, by extension, the security of the world.